Modified stoke ankylosing spondylitis spinal score as an outcome measure to assess the impact of treatment on structural progression in ankylosing spondylitis. (30th May 2018) - van der Heijde, Désirée; Braun, Jürgen; Deodhar, Atul; Baraliakos, Xenofon; Landewé, Robert; Richards, Hanno B; Porter, Brian; Readie, Aimee
Abstract: In ankylosing spondylitis (AS), structural damage that occurs as a result of syndesmophyte formation and ankylosis of the vertebral column is irreversible. Structural damage is currently assessed by conventional radiography and scoring systems that reliably assess radiographic structural damage are needed to capture the differential effects of drugs on structural damage progression. The validity of the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) as a primary outcome measure in evaluating the effect of AS treatments on radiographic progression rates was assessed in this review. The mSASSS has not been used, to date, as a primary outcome measure in a prospective randomized controlled clinical trial of biologic therapy in AS. This review of the medical literature confirmed that the mSASSS is the most validated and widely used method for assessing radiographic progression in AS, correlating with worsening measures of disease signs and symptoms, spinal mobility and physical function, with a 2-year interval being required to ensure sufficient sensitivity to change.